Applications of Mathematical Control Theory to Accounting and Budgeting (The Continuous Wheat Trading Model). - Ijiri, Yuji; Thompson, Gerald L. (The Accounting Review, 1970)
The article applies mathematical control theory to the analysis of a simple model of an accounting and budgeting problem. The objective is not only to make the model operational for practical applications but also to use the framework and results of mathematical control theory in order to get new insights into accounting and budgeting problems. The article shall be primarily concerned with the process of the operations of the firm looked at from an accounting standpoint. In accounting, a firm is represented by a set of quantities that indicate the stocks of assets of various types that are under the control of the firm and the firm's activities are indicated by the changes in these quantities. Using mathematical notation one can say that the firm at time t has a vector x(t) whose components indicate the physical amounts of each asset the firm has at time t. The results of the activities of the firm between t1 and t2 are measured by the vector difference x(t2)-x(t1). It is found that firm's activities at time t are indicated by &xdot;(t), which in turn affects x(t).